PERSEPSI APARATUR PEMERINTAH TENTANG KUALIFIKASI PROFESI HUMAS - Kokom Komariah; Aat Ruchiat Nugraha; Susie Perbawasari (Avant Garde, 2016)
There are still many differences in the views of the public relations profession, namely as a "handyman" read the news, frontline, photographer, maker of the press conference, reception, to the functions of public relations as a strategic planner in the decision-making body or a part of the dominant coalition. Perceptions of a profession that is contained in an organization, it is significant because it may affect how a person appreciate the work or duties, and qualifications of the professional field. This research was conducted in order to reveal the existence of phenomena that occur on the Public Relations profession in the District Government Pangandaran. The method used in the form of quantitative methods and the types of descriptive survey study. The respondents were selected were government officials working in the district administration Pangandaran with data collection is done by means of the distribution of questionnaires, interviews, observation, and literature studies. The results showed that the apparatus of government in the district of Pangandaran has to perceive / interpret the qualifications Public Relations profession is well on aspects of the ability to communicate, ability to organize, ability to get on with people, and imagination. However, in the aspect of personal integrity there that consider a Public Relations officials do not have to come from public relations education / communication and should not be a woman.